Clinical diagnosis and endoscopic analysis of 10 cases of intestinal tuberculosis. Issue 28 (10th July 2020) - Lu, Shuangshuang; Fu, Jinjin; Guo, Yongxin; Huang, Jin
Abstract : Abstract: To analyze the clinical characteristics of intestinal tuberculosis (ITB), pay attention to the diagnostic value of endoscopy and mucosal biopsy, improve the recognition of atypical manifestations of ITB under endoscopy, and reduce misdiagnosis and missed diagnosis. The clinical data of 10 patients who were hospitalized in Changzhou second people's Hospital and finally diagnosed as ITB from January 1, 2015 to present were analyzed retrospectively. The basic information, medical history, clinical manifestations and computed tomography (CT), endoscopy of the patients was analyzed retrospectively. The results of pathological examination were analyzed and sorted out. Among the 10 patients, the ratio of male to female was 7:3, 10 (100%) had abdominal pain, 3 (30%) had diarrhea and 2 (20%) had bloody stool. The positive rate of tuberculosis T cell test was 75% (6/8), the diagnostic rate of chest high resolution CT was 60%, and the abnormal rate of abdominal high-resolution CT was 66.7% (6/9). Colonoscopy showed that the lesions mainly involved ileocecum (70%) and ascending colon (60%). Most of the lesions were intestinal stenosis (60%) and circular ulcer (50%). In a few cases, cold abscess (20%) and scar diverticulum (10%). Most of the pathological manifestations were granuloma formation and multinucleated giant cells (60%). The detection rate of caseous granuloma was 20%. The general condition and clinical manifestations of patients with ITB are not specific. Endoscopy and mucosal biopsy are of great significance for its diagnosis. The clinical manifestations and endoscopy of some patients showed atypical signs. Therefore, the combination of multi-disciplinary team models and the enhancement of clinician's recognition of the characteristics of endoscopic examination of ITB can improve us the diagnosis level of ITB.